Benign bone tumors--recent developments - Garcia, Roberto A; Inwards, Carrie Y; Unni, Krishnan K (Seminars in diagnostic pathology, 2011)
Benign bone tumors frequently pose a diagnostic challenge for general surgical pathologists. Accurate pathologic diagnosis requires careful clinical and radiological correlation. The most significant recent advances in some benign bone tumors have occurred at the molecular and cytogenetic level. The detection of clonal chromosomal aberrations, various specific molecular genetic events, and the description of the bone cell signaling pathways in the field of osteoimmunology have provided a better understanding of the pathophysiology of certain tumors and an important aid in the diagnostic workup and differential diagnosis of some bone lesions demonstrating overlapping clinical and pathologic features. Future directions include prognostic and therapeutic applications of these findings. Newer less invasive therapeutic techniques and medical management have been developed for the treatment of certain benign bone tumors.